2013
DOI: 10.1007/s11434-013-5933-9
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillogenesis regulator-1 promotes cell adhesion and migration in human hepatoma cells

Abstract: Myofibrillogenesis regulator-1 (MR-1) is a gene overexpressed usually in many human cancers. However, the effects of MR-1 on cell proliferation, adhesion, migration and genome-wide gene regulation are still unclear. In this study, a human hepatoma cell line that highly overexpresses MR-1, BEL-7402/MR-1 cells was established. While the high expression of MR-1 did not promote cell proliferation, it significantly increased cell spreading, adhesion and migration compared with control cells. A total of 147 genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The Hippo pathway plays an important role in cell proliferation, differentiation and DNA damage, and YAP is the major downstream effector of the Hippo pathway [ 31 33 ]. Some studies showed that YAP participated in DNA damage-induced apoptosis and is the key role in tumor suppression independent of p53, YAP knockdown sensitized tumor cells to chemotherapy and radiation effects via increased accumulation of DNA damage [ 14 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hippo pathway plays an important role in cell proliferation, differentiation and DNA damage, and YAP is the major downstream effector of the Hippo pathway [ 31 33 ]. Some studies showed that YAP participated in DNA damage-induced apoptosis and is the key role in tumor suppression independent of p53, YAP knockdown sensitized tumor cells to chemotherapy and radiation effects via increased accumulation of DNA damage [ 14 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whole-cell lysates were used for immunoblotting as described previously [ 14 ]. Cells were lysed using lysis buffer (50 mmol/L Tris-HCl (pH 8.0), 150 mmol/L sodium chloride, 1.0% Triton X-100, 0.5% sodium deoxycholate, 0.1% SDS, protease inhibitor), and 20 μg of protein lysate was resolved by SDS-PAGE and analyzed by immunoblotting with specified antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Cell growth inhibition was determined by using a SRB assay [ 11 ]. Cells were seeded in 96-well plates at 4 × 10 3 –8 × 10 3 /well and treated with the increasing concentrations of compound IMB-HDC and incubated for 24 h or 48 h, then cells were fixed with 50% trichloroacetic acid (TCA) (Sigma-Aldrich, Saint Louis, MO, USA), and then 0.4% (w/v) SRB in acetic acid (1%) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Cell growth inhibition was determined using sulforhodamine B (SRB) assay. 9 Cells were seeded in 96-well plates at 4×10 3 –8×10 3 /well, and were treated with increasing concentrations of compound 05D and incubated for 24 or 48 hours. The cells were fixed with 50% trichloroacetic acid (Sigma-Aldrich), and then 0.4% (w/v) SRB in acetic acid (1%) was added.…”
Section: Methodsmentioning
confidence: 99%